International Students in Ontario Secondary Schools: Demystifying the Stereotype - Schecter, Sandra; Merecoulias, Maria (Comparative and International Education / Éducation comparée et internationale, 2023)
This article addresses findings of a study focused on the schooling experiences and social and cultural adaptation of international students who have come to Canada to learn English and obtain an Ontario Secondary School Diploma. Nonnative speakers of English and noncitizens of Canada, they are brought to Canada by relatives or recruitment agents who depart after installing them with host families with whom they have had virtually no previous contact. Respondents, mostly professional educators and focal students, describe considerable sacrifices the youths’ parents have made in the hope that acquisition of “legitimate” English will give their child access to global citizenship and a secure future. Adult respondents emphasized how many early study abroad students experience difficulties with second language socialization, with a significant minority considered “at risk” for academic failure. Testimony from educators described adaptation issues, including: loneliness and disorientation, stresses from pressure to succeed academically, and inadequate homestay conditions. Students’ responses revealed considered decisions resulting from strategic weighting of options and choices. Respondents found differing and inconsistent policies and protocols among educational providers and lack of adequate oversight to be key explanatory factors for the issues confronting secondary-level international students.